An efficient approach to the determination of Equivalent Static Wind Loads. (January 2017) - Patruno, L.; Ricci, M.; Miranda, S. de; Ubertini, F.
Abstract: In this paper, a novel approach to the determination of Equivalent Static Wind Loads is presented. The envelope of the effects on the structure, representing the design load for each structural member and obtained by means of a complete buffeting analysis, is reconstructed, in a least square sense, by considering a series of statically applied load conditions. Such load conditions are obtained by combining Principal Static Wind Loads which, in turn, are obtained by means of the recently introduced Proper Skin Modes. By considering a smoothed version of the maximum/minimum operator, efficient, gradient based, optimization algorithms can be used in order to drive the least square minimization which conduces to the identification of the most significant wind load conditions. Such load conditions, statically applied, can be used in order to fully characterize the effect of the wind on the structure with very good approximation. No hypotheses are introduced regarding the shape of the envelopes, so rendering the procedure of general applicability. Very good results in terms of reconstruction rate and accuracy are obtained on a low-rise and a high-rise buildings. Abstract : Highlights: A new approach for the determination of Equivalent Static Wind Loads is proposed. Principal Static Wind Loads are defined starting from a few predefined pressures distributions. Equivalent Static Wind Loads are easily and efficiently extracted. No hypothesis is introduced regarding the shape of the envelope of the effects on the structure.